Head to toe science : over 40 eye-popping, spine-tingling, heart-pounding activities that teach kids about the human body - Wiese, Jim, 1948- (New York : J. Wiley, 2000)
Introduces the circulatory system, muscles, digestion, senses, and other body parts and functions through a collection of activities and experiments which can be developed into science fair projects.
Includes index.
Booklist.
Library Talk.
School Library Journal.
5.0
3-6
Keywords: Human body -- Juvenile literature; Human physiology -- Juvenile literature; Science projects -- Juvenile literature; Experiments; Human body -- Experiments; Human physiology -- Experiments; Science projects; Human body -- Experiments; Physiology -- Experiments; Science projects; Science -- Experiments